Preparing for a career in engineering - 20160731 frey50; J.G. Ferguson Publishing Company (Chicago, Ill. : Ferguson Pub., 1998)
Explores career opportunities in the field of engineering, provides a detailed look at eight specific occupations, discussing education and training needed, skills required, and salary ranges, and offers advice on steps to prepare for a career.
Includes index.
Keywords: Engineering -- Vocational guidance -- Juvenile literature; Engineering -- Vocational guidance; Vocational guidance